Tanggung Jawab Pelaku Usaha Maskapai Penerbangan atas Penundaan Pembayaran Dana Refund - Dinda Aurelia Danian; Ni Luh Made Mahendrawati; Ida Ayu Putu Widiati (Warmadewa Press, 2021)
Competition encourages companies to provide attractive offers such as promo ticket prices to giving free seats. However, many airline companies, who only want to achieve their profit targets, are willing to put aside their responsibilities and consumer rights; one of which is the delay of a flight ticket refund due to the cancellation of the flight by the airline unilaterally. This study aims to determine the form of legal protection for consumers who experience delays in paying Refund funds by airlines and to find out the forms of airline responsibility for Refund funds and settlement efforts in case of disputes. This type of research is normative juridical with a statutory approach presented in the form of legal interpretation. The results showed that the cancellation of flight schedules by airlines was not regulated in Law No. 1 of 2009 concerning Aviation, but the provisions can be seen in the Minister of Transportation Regulation Number 77 of 2011 Article 12 paragraphs 1 and 2. Permenhub Number 185 of 2015 also regulates the period of ticket refunds. Refunds can also be added with other compensation as well as Article 1453 of the Civil Code. The time period for the refund process by airlines is generally in accordance with the Regulation of the Minister of Transportation Number 185 of 2015. Settlement of consumer disputes can be done by 1) Direct compensation for losses; 2) Through BPSK by means of mediation, conciliation and arbitration; 3) Settlement of consumer disputes through litigation.